Tinjauan Sharia Compliance terhadap Praktik Transaksi dalam Pembelian Hewan Kurban dengan Akad Murabahah di Aplikasi Instagram: (Studi Kasus di 7gembalafarm) - Saleh, Mulyana; Agustine, Hendra Karunia; Fakhlevi Suwondo, Izzy Dwiki (AL-MASHALIH (Journal of Islamic Law), 2024)
Buying and selling is the most extensive gateway or door to transactions. The phenomenon of buying and selling in Islam has certainly experienced many changes and advances. Buying and selling transactions no longer rely on face-to-face buying and selling. One of those who take advantage of this progress in buying and selling is 7gembalafarm, where 7gembalafarm provides various types of sacrificial animals and sells them online through the marketplace, one of which is Instagram. The problem that arises is whether the application of the murabahah contract in the sale and purchase of sacrificial animals at 7gembalafarm is in accordance with sharia compliance so that people feel calm when buying sacrificial animals at 7gembalafarm and whether the application of transactions with the murabahah contract in the sale and purchase of sacrificial animals on the Instagram application is in accordance with sharia compliance or not, and can it cause potential usury elements or not, because these things are still uncertain. This study aims to determine how the transaction practices in purchasing sacrificial animals with the murabahah contract at 7gembalafarm and how the sharia compliance review of transaction practices in purchasing sacrificial animals with the murabahah contract at 7gembalafarm. This study uses a qualitative method with a field research type. The data collection techniques used are interviews and documentation. The results of this study are: First, the transactions carried out by 7gembalafarm have been carried out transparently in explaining the types of transactions so that no one is harmed and there is a third party paylater in the transaction. Second, based on a review of sharia compliance with the purchase of sacrificial animals with a murabahah contract, when viewed from sharia compliance, it is not in accordance with the principles in sharia compliance because one of the principles of sharia compliance must be free from usury. Thus, the transactions at 7gembalafarm are not 100% in accordance with Sharia compliance because 7gembalafarm uses a third party paylater in its transactions.